Association of clinical signs of possible serious bacterial infections identified by community health workers with mortality of young infants in South Asia: a prospective, observational cohort study - Darmstadt, Gary L.; Ahmed, Saifuddin; Islam, Mohammad Shahidul; Abdalla, Safa; El Arifeen, Shams; Arvay, Melissa L.; Baqui, Abdullah H.; Bhutta, Zulfiqar A.; Bose, Anuradha; Connor, Nicholas E.; Hossain, Belal; Isaac, Rita; et al. (EClinicalMedicine, 2025)
The World Health Organization (WHO) has developed guidance for community health workers (CHWs) in identifying sick young infants based on clinical signs. We conducted a prospective, observational cohort study to characterise mortality risk of young infants based on their clinical signs. We conducted a population-based, prospective observational cohort study at five sites in Bangladesh (Sylhet, November 01, 2011–December 31, 2013), India (Vellore and Odisha, September 01, 2013–February 28, 2015), and Pakistan (Karachi, January 01, 2012–December 31, 2013; Matiari, March 01, 2012–December 31, 2013) to identify newborn infants who were followed-up by CHWs through 10 scheduled home visits over the first 60 completed days after birth to identify signs of possible serious bacterial infection (PSBI). We determined the frequency of signs and conducted Cox regression to investigate the association of signs with mortality risk within 7 days of identification of the signs. CHWs made 522,309 visits to assess 63,017 young infants and found ≥1 sign(s) of PSBI at 14,245 visits (2.7%), including 5.8% (5568 of 96,390) and 1.8% (6635 of 365,769) of visits of infants 0–<3 and 7–<60 days of age, respectively. Each of the seven signs of PSBI when found alone was associated with significantly (p < 0.0001) increased risk for mortality, which increased further if any other additional sign of PSBI was found concurrently. Over the young infant period (days 0–<60) CHW identification of no movement or movement only on stimulation was associated with the highest risk for mortality [adjusted hazard ratio (aHR) 73.0, 95% confidence interval (CI) 44.4–119.9] followed by poor feeding (aHR 31.9, 95% CI 24.1–42.3) and hypothermia (<35.5 °C) (aHR 31.4, 95% CI 23.5–41.9). Hypothermia had particularly high risk for mortality during days 7–<60 (HR 45.1, 95% CI 27.6–73.4). WHO reconsideration of hypothermia as a sign of critical illness is warranted. Implementation research is urgently needed to reduce infant mortality by ensuring immediate referrals and interventions for children identified early by CHWs with no movement or movement only on stimulation, hypothermia, or poor feeding, especially in resource-poor settings. Bill and Melinda Gates Foundation, New Venture Fund for Global Policy and Advocacy.